Efficacy and safety of the CVnCoV SARS-CoV-2 mRNA vaccine candidate in ten countries in Europe and Latin America (HERALD): a randomised, observer-blinded, placebo-controlled, phase 2b/3 trial. Issue 3 (March 2022) - Kremsner, Peter G; Ahuad Guerrero, Rodolfo Andrés; Arana-Arri, Eunate; Aroca Martinez, Gustavo Jose; Bonten, Marc; Chandler, Reynaldo; Corral, Gonzalo; De Block, Eddie Jan Louis; Ecker, Lucie; Gabor, Julian Justin; Garcia Lopez, Carlos Alberto; Gonzales, Lucy; et al.
Summary: Background: Additional safe and efficacious vaccines are needed to control the COVID-19 pandemic. We aimed to analyse the efficacy and safety of the CVnCoV SARS-CoV-2 mRNA vaccine candidate. Methods: HERALD is a randomised, observer-blinded, placebo-controlled, phase 2b/3 clinical trial conducted in 47 centres in ten countries in Europe and Latin America. By use of an interactive web response system and stratification by country and age group (18–60 years and ≥61 years), adults with no history of virologically confirmed COVID-19 were randomly assigned (1:1) to receive intramuscularly either two 0·6 mL doses of CVnCoV containing 12 μg of mRNA or two 0·6 mL doses of 0·9% NaCl (placebo) on days 1 and 29. The primary efficacy endpoint was the occurrence of a first episode of virologically confirmed symptomatic COVID-19 of any severity and caused by any strain from 15 days after the second dose. For the primary endpoint, the trial was considered successful if the lower limit of the CI was greater than 30%. Key secondary endpoints were the occurrence of a first episode of virologically confirmed moderate-to-severe COVID-19, severe COVID-19, and COVID-19 of any severity by age group. Primary safety outcomes were solicited local and systemic adverse events within 7 days after each dose and unsolicited adverse events within 28 days after each dose in phase 2b participants, and serious adverse events and adverse events of special interest up to 1 year after the second dose in phase 2b and phase 3 participants. Here, we report data up to June 18, 2021. The study is registered at ClinicalTrials.gov, NCT04652102, and EudraCT, 2020–003998–22, and is ongoing. Findings: Between Dec 11, 2020, and April 12, 2021, 39 680 participants were enrolled and randomly assigned to receive either CVnCoV (n=19 846) or placebo (n=19 834), of whom 19 783 received at least one dose of CVnCoV and 19 746 received at least one dose of placebo. After a mean observation period of 48·2 days (SE 0·2), 83 cases of COVID-19 occurred in the CVnCoV group (n=12 851) in 1735·29 person-years and 145 cases occurred in the placebo group (n=12 211) in 1569·87 person-years, resulting in an overall vaccine efficacy against symptomatic COVID-19 of 48·2% (95·826% CI 31·0–61·4; p=0·016). Vaccine efficacy against moderate-to-severe COVID-19 was 70·7% (95% CI 42·5–86·1; CVnCoV 12 cases in 1735·29 person-years, placebo 37 cases in 1569·87 person-years). In participants aged 18–60 years, vaccine efficacy against symptomatic disease was 52·5% (95% CI 36·2–64·8; CVnCoV 71 cases in 1591·47 person-years, placebo, 136 cases in 1449·23 person-years). Too few cases occurred in participants aged 61 years or older (CVnCoV 12, placebo nine) to allow meaningful assessment of vaccine efficacy. Solicited adverse events, which were mostly systemic, were more common in CVnCoV recipients (1933 [96·5%] of 2003) than in placebo recipients (1344 [67·9%] of 1978), with 542 (27·1%) CVnCoV recipients and 61 (3·1%) placebo recipients reporting grade 3 solicited adverse events. The most frequently reported local reaction after any dose in the CVnCoV group was injection-site pain (1678 [83·6%] of 2007), with 22 grade 3 reactions, and the most frequently reported systematic reactions were fatigue (1603 [80·0%] of 2003) and headache (1541 [76·9%] of 2003). 82 (0·4%) of 19 783 CVnCoV recipients reported 100 serious adverse events and 66 (0·3%) of 19 746 placebo recipients reported 76 serious adverse events. Eight serious adverse events in five CVnCoV recipients and two serious adverse events in two placebo recipients were considered vaccination-related. None of the fatal serious adverse events reported (eight in the CVnCoV group and six in the placebo group) were considered to be related to study vaccination. Adverse events of special interest were reported for 38 (0·2%) participants in the CVnCoV group and 31 (0·2%) participants in the placebo group. These events were considered to be related to the trial vaccine for 14 (<0·1%) participants in the CVnCoV group and for five (<0·1%) participants in the placebo group. Interpretation: CVnCoV was efficacious in the prevention of COVID-19 of any severity and had an acceptable safety profile. Taking into account the changing environment, including the emergence of SARS-CoV-2 variants, and timelines for further development, the decision has been made to cease activities on the CVnCoV candidate and to focus efforts on the development of next-generation vaccine candidates. Funding: German Federal Ministry of Education and Research and CureVac.